LIFE NARRATIVES OF FILIPINO TRICYCLE DRIVERS: CONTENTMENT, REGRETS AND REALIZATIONS IN THE PANDEMIC - Rosal, Mel Rose; Bagaporo, Evelyn; Rungduin, Teresita (International Journal of Arts, Sciences and Education, 2024)
Tricycle drivers are individuals who drive tricycles for a living. In this study, it explored the life narratives of ten (10) Filipino tricycle drivers in Silang, Cavite about their experiences before and during the epidemic, focusing on their contentment and regrets in their personal and professional lives. It also examined how their viewpoints changed and the realizations they have had as a result of their particular experiences brought on by the epidemic. Four themes were generated from their life experiences before and during pandemic which were: An Early Riser and Late Sleeper, Challenged Livelihood, The Need to be Contented and Principle-Oriented. Despite being common to see on roads, studies about their life experiences are seldom rare. This study advocates for increased awareness among community commuters, governmental respect, and the implementation of intervention programs to support tricycle drivers, challenging societal perceptions and affirming the respectability of their profession.